A new coumarin-based fluorescent probe for selective recognition of Cu2+ and S2− in aqueous solution and living cells. Issue 30 (26th July 2019) - Liu, Zhen; Liu, Linjing; Li, Jiulong; Qin, Yuanyuan; Zhao, Chenyang; Mi, Yang; Li, Guoping; Li, Tiesheng; Wu, Yangjie
Abstract: A new coumarin-based fluorescent probe CMOH was easily synthesized for detection of Cu 2+ and S 2− in aqueous media and living cells. CMOH displayed high sensitivity (detection limit = 3.2 nM) and selectivity to Cu 2+ with a non-fluorescence complex CMOH-Cu 2+ formation via a 1:1 binding mode. According to displacement approach, the fluorescence of CMOH-Cu 2+ was recovered in the presence of S 2− and acted as a sensitive sensor with a low detection limit of 11.4 nM. This ''on-off-on'' process can be accomplished within 1 min and repeated at least 5 times. What's more, CMOH exhibited good permeability, low cytotoxicity and can be used as a suitable tool to detect changes of Cu 2+ and S 2− in biosystem. Graphical abstract: A novel coumarin-based fluorescent probe for detection of Cu 2+ and S 2- in aqueous media and living cells. Image 1 Highlights: A new coumarin-based fluorescent probe CMOH for sequential detection of copper ion and sulfide. The probe displayed high sensitivity, selectivity, good water-solubility, short response time and reversible detection. The DFT calculation and 1 H NMR analysis also performed to further investigate the sensing mechanism. The probe CMOH can be a suitable tool for sequential investigation of Cu 2+ and S 2- in living cells with low cytotoxicity.